Genome Sequence of Bifidobacterium breve DPC 6330, a Strain Isolated from the Human Intestine - Guinane, Caitriona M. (American Society for Microbiology, 2011)
The draft genome of Bifidobacterium breve DPC 6330, isolated from an elderly patient, was determined. B. breve DPC 6330 was previously identified to synthesize the beneficial metabolite conjugated linoleic acid from free linoleic acid. The sequence will allow identification and characterization of the genetic determinants of its putative beneficial properties.